2012
DOI: 10.1167/iovs.12-9917
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional, Optical Sign-Dependent Regulation of BMP2 Gene Expression in Chick Retinal Pigment Epithelium

Abstract: That mRNA expression of BMP2 in chick RPE shows bidirectional, defocus sign-dependent changes is suggestive of a role for BMP2 in eye growth regulation, although the diffuse ocular expression of BMP2 and its receptors suggests complex growth-modulatory signal pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 47 publications
11
76
1
Order By: Relevance
“…This testing strategy reduces the influence of inter-animal variability, but leaves open the question of whether the behavior of the fellow eyes was normal. Although some studies using this chick model for myopia have reported interocular (yoking) interactions (Zhang, Liu, & Wildsoet, 2012), a previous study involving mechanical testing of strips of chick sclera observed no statistical difference between contralateral controls and eyes from untreated, normal chicks (Phillips et al, 2000). …”
Section: Discussionmentioning
confidence: 85%
“…This testing strategy reduces the influence of inter-animal variability, but leaves open the question of whether the behavior of the fellow eyes was normal. Although some studies using this chick model for myopia have reported interocular (yoking) interactions (Zhang, Liu, & Wildsoet, 2012), a previous study involving mechanical testing of strips of chick sclera observed no statistical difference between contralateral controls and eyes from untreated, normal chicks (Phillips et al, 2000). …”
Section: Discussionmentioning
confidence: 85%
“…33 Finally, recent studies have demonstrated differential expression of a number of genes in the RPE of eyes undergoing experimental manipulations perturbing normal eye growth. 34,35 …”
Section: The Role Of the Rpe In Eye Growth Regulationmentioning
confidence: 99%
“…Although changes in levels of proteins or other molecules presumably are key to actually transmitting signals from choroid to sclera, it has been found that changes in mRNA levels can identify the responses of the cells in tissues and are useful in identifying pathways of interest (Gao et al, 2011, 2013; Schippert et al, 2006; Shelton et al, 2008; Siegwart & Norton, 2005; Stone et al, 2011; Zhang, Liu, & Wildsoet, 2012). In a previous paper in tree shrew choroid (He et al, 2014), we examined the gene expression signatures produced by ML wear (GO) and by recovery from induced myopia (a STOP condition).…”
Section: Introductionmentioning
confidence: 99%